Pahlawan Pejuang Maluku Utara: Pengenalan dan Workshop Penulisan Biografi kepada Siswa SMA Negeri 4 Halmahera Selatan - Barjiyah, Umi; Putri, Sri Haryati (Pencerah, 2025)
Every individual has a unique story and life background. Therefore, introducing local heroes to the younger generation in East Gane is of great importance. As part of North Maluku, South Halmahera holds the responsibility to preserve its history and elevate local figures as sources of inspiration and learning. Through educational institutions such as SMAN 4 South Halmahera, students can be nurtured to become future leaders who are not only intellectually capable but also rooted in historical awareness and local wisdom. In implementing this initiative, it is essential not only to share the heroic stories of North Maluku’s figures but also to teach the art of writing biographies. Writing a life story is one of the most effective ways to bring these values into the heart of the community. Through written texts, a person's life journey can be immortalized—not merely as a historical record, but as a reflection of courage, virtue, and a fighting spirit worthy of emulation.